2007
DOI: 10.1097/01.ccm.0000282073.98414.4b
|View full text |Cite
|
Sign up to set email alerts
|

Severe hypoglycemia in critically ill patients: Risk factors and outcomes*

Abstract: Case-control methodology and multivariable logistic regression analysis concurred that even a single episode of severe hypoglycemia was independently associated with increased risk of mortality. Safe implementation of tight glycemic control requires appropriate monitoring to reduce the risk of this complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
398
4
27

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 592 publications
(441 citation statements)
references
References 27 publications
12
398
4
27
Order By: Relevance
“…As previously reported, the IGC procedure becomes very difficult in the medical ICU, especially in patients who have sepsis, a high APACHE score or mechanical ventilation. 1,2,22,23 The low rate of hypoglycemia could be because the medical acuity of our patients were relatively mild compared to those of patients in the medical ICU. Moreover, patients undergoing HSCT are younger and might have better b-cell function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously reported, the IGC procedure becomes very difficult in the medical ICU, especially in patients who have sepsis, a high APACHE score or mechanical ventilation. 1,2,22,23 The low rate of hypoglycemia could be because the medical acuity of our patients were relatively mild compared to those of patients in the medical ICU. Moreover, patients undergoing HSCT are younger and might have better b-cell function.…”
Section: Discussionmentioning
confidence: 99%
“…The low rate of hypoglycemia could be important for maximizing the benefit of IGC because severe hypoglycemia could be associated with an increased risk of mortality. 23 Values are mean þ s.e.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of ICU patients have found an association between hypoglycemia and both sepsis and circulatory shock [6,7]. All six such patients were non-diabetic, which reinforces the need for increased vigilance and monitoring of this group of patients, in whom metabolic derangements and hypoglycemia may be associated with increased mortality [8]. It is not clear what role these events played in the hospital course of these patients whose expected mortality would have been very high.…”
Section: Failure To Monitor -Patients 2 3 4 6 and 15mentioning
confidence: 99%
“…In der Gruppe mit enger Blutzuckereinstellung erhöhte sich das Risiko für nichterkannte Hypoglykämien [690,691,692]. Schwere Hypoglykämie ist wiederum mit einer gesteigerten Mortalität bei schwer kranken Patienten assoziiert, wobei besonders bei Bewusstlosen das Risiko von unbeobachteten Hypoglykämien besteht [693]. Es besteht Evidenz, dass unabhängig vom Zielbereich, eine Variabilität bei den Blutzuckerwerten mit einer erhöhten Mortalität assoziiert ist [694].…”
Section: Behinderung (Optimierung Der Neurologischen Erholung) Zerebrunclassified